Struktur dan Peran Spora pada Thallophyta dan Bryophyta : Analisis Morfologi dan Reproduksi (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2024)
This study analyzes the structure and role of spores in Thallophyta and Bryophyta in reproduction and ecosystem adaptation. Spores in Bryophyta, such as mosses, play an important role in dispersal and colonization in extreme environments, with the sporangium being the site of formation. In Thallophyta, spores function as asexual reproductive units, supporting dispersal through water and air media. Spores exhibit distinctive morphologies that favor reproductive efficiency. The results confirm that spores play a vital role in the continuity of generations and the ecological contribution of lower plants.